Association of exposure to air pollutants with gestational diabetes mellitus in Chiayi City, Taiwan - Yan, Yuan-Horng; Chien, Chu-Chun; Wang, Panchalli; Lu, Mei-Chun; Wei, Yu-Ching; Wang, Jyh-Seng; Wang, Jun-Sing (Frontiers in Endocrinology, 2023)
We investigated the associations of exposure to particulate matter with an aerodynamic diameter less than 2.5 μm (PM2.5) and several gaseous pollutants with risk of gestational diabetes mellitus (GDM) in Taiwan. We retrospectively identified pregnant women who underwent a two-step approach to screen for GDM between 2006 and 2014. Information on concentrations of air pollutants (including PM2.5, sulfur dioxide [SO2], nitrogen oxides [NOx], and ozone [O3]) were collected from a single fixed-site monitoring station. We conducted logistic regression analyses to determine the associations between exposure to air pollutants and risk of GDM. A total of 11210 women were analyzed, and 705 were diagnosed with GDM. Exposure to PM2.5 during the second trimester was associated with a nearly 50% higher risk of GDM (odds ratio [OR] 1.47, 95% CI 0.96 to 2.24, p=0.077). The associations were consistent in the two-pollutant model (PM2.5 + SO2 [OR 1.73, p=0.038], PM2.5 + NOx [OR 1.52, p=0.064], PM2.5 + O3 [OR 1.96, p=0.015]), and were more prominent in women with age <30 years and body mass index <25 kg/m2 (interaction p values <0.01). Exposure to PM2.5 was associated with risk of GDM, especially in women who were younger or had a normal body mass index.